Damage and fracture of brittle materials subjected to tri-axial compression - Litewka, A.; Szojda, L. (Archives of Mechanics, 2005)
The aim of the paper is to present the experimental and theoretical study of fracture of brittle materials. To this end, new and more complete experimental data on deformability and fracture of brick and mortar subjected to tri-axial state of stress were discussed. Such experimental data are necessary to formulate the theoretical models capable of describing the mechanical behaviour of concrete, cementitious composites, ceramics and rocks. The second objective of this study is to present the potentialities of our own phenomenological model, based on continuum damage mechanics and on the theory of tensor function representation. Comparison of the experimental results obtained for tri-axial compression of brick and mortar with respective theoretical predictions showed satisfactory agreement.